TRANSPORT MORFOGEN MELALUI PLASMODESMATA DAN PERANNYA DALAM PEMBENTUKAN POLA PADA Arabidopsis thaliana: SUATU KAJIAN PUSTAKA - Liya Tri Wahyuni; Syafi'i, Wan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Morphogens are signaling molecules that provide positional information to determine cell fate and tissue patterning in plants, and in Arabidopsis thaliana, the distribution of these molecules is tightly regulated to ensure developmental stability. This study aims to review the mechanisms of morphogen transport through plasmodesmata and their role in patterning within Arabidopsis thaliana using a literature review method that synthesizes recent findings on symplastic transport, callose regulation, and tissue-specific signaling. Findings indicate that morphogen distribution, including auxin, brassinosteroids, and regulatory proteins like WUSCHEL, occurs through parallel pathways involving both active transport and passive diffusion via plasmodesmata, which is dynamically controlled by callose deposition and degradation at the plasmodesmal neck acting as a biological valve. Furthermore, tissue-specific regulators such as PDLP6 facilitate precise flux control within the vasculature, leading to the conclusion that plasmodesmata-mediated transport is essential for creating accurate concentration gradients to provide positional information, ensuring robust development and enabling morphological diversity through the modulation of symplastic connectivity.